Association of Lhermitte-Duclos and Cowden disease: report of a new case and review of the literature. Issue 6 (June 1994) - Vinchon, M; Blond, S; Lejeune, J P; Krivosik, I; Fossati, P; Assaker, R; Christiaens, J L
Abstract : Lhermitte-Duclos disease is a rare entity, and its pathological features are unique. Pathological findings are characteristic of the disease, with global hypertrophy of the cerebellum, coarse gyri, and the typical "inverted cortex" pattern. Several associated lesions were noted in many patients with Lhermitte-Duclos disease. It is only recently that an association between Lhermitte-Duclos disease and Cowden disease was reported. Cowden disease, or multiple hamartomas syndrome, is a familial disease associating breast cancer, cutaneomucous tricholemmomas, and various other tumoural and dysplasic conditions. A new case of Lhermitte-Duclos disease associated with Cowden disease is reported. A review of the literature found 72 cases of Lhermitte-Duclos disease; 26 had conditions suggesting Cowden disease and seven were definite cases of Cowden disease. The association of Lhermitte-Duclos disease and Cowden disease is probably underestimated. Cowden disease represents a new form of phakomatosis; Lhermitte-Duclos disease may occur as a sporadic disease, or as part of familial Cowden disease. The possibility of preneoplastic states in Cowden syndrome stresses the importance of a thorough screening when Lhermitte-Duclos disease is diagnosed.